Pengaruh Literasi Keuangan, Sikap Keuangan dan Self-Efficacy terhadap Pengelolaan Keuangan Ibu Rumah Tangga - Pradinaningsih, Novia Ayu; Wafiroh, Novi Lailiyul (E-Jurnal Akuntansi, 2022)
This research is aims to determinate the effect of financial literacy and financial attitudes on homemakers financial management with self-efficacy as moderating variabel. The approach method in this reseach is the quantitative approach using the WarpPLS 7.0 analysis program. Methods of data collection using a questionnaire. The sample of this research is 148 houswives in Perumahan Green Bangil. The study result shows that financial literacy, financial attitudes, and self-efficacy have a significant effect on financial management of homemakers, financial literacy and financial attitudes do not affect effect on the financial management of homemakers moderated by self-efficacy. Keywords: Financial Literacy; Financial Attitudes; Financial Management of Homemakers; Self-Efficacy.